Estudio de factibilidad para la implementación de una infraestructura de hiperconvergencia de alta disponibilidad en la Data Center Experimental - Santana Lasluisa, Bryan Javier (2019)
This document seeks the study for the design of an hyperconvergent infrastructure with high availability for the Experimental Data Center of the Universidad de las Américas, located in the city of Quito, Ecuador. First, there will be a brief introduction to the history of the data centres to date, as well as an explanation of the classification of the data centres and an analysis of current trends. An inventory will be made of the existing infrastructure in the data center, as well as explaining the detailed characteristics of the equipment and reviewing the technology which they are virtualized. On the other hand, a survey of the current hyperconvergence market will be reviewed, thanks to the Gartner quadrant, the three leading market solutions will be studied and the strengths and weaknesses of each of the hyperconvergent solutions will be pointed out. Finally, a hyperconvergent infrastructure solution will be designed based on the existing technical specifications in the data center; in addition, a technicaleconomic study will be carried out.